ANALYSIS OF TOURIST TRAFFIC IN SERBIA AND ITS IMPACT ON ECONOMIC DEVELOPMENT - Gajić, Tamara; Džigurski, Anđelija; Dragin, Aleksandra (Economics of Agriculture, 2011)
Tourism is by many of its features and performance in the world marked the 20th century, and from its appearance until today follows the tourism and creates an expansive variety of social and economic phenomena. A large number of studies related to its economic effects, which are actually related to its growth and development, organization, management, business and entrepreneurial and technical aspects and interpretation. The economic nature of tourism has remained a fundamental fact, and now that scholars are increasingly examining the social effects of this activity. The place and role of tourism and hospitality industry in the economic development of Serbia was an important issue that deserves special attention and that is the subject of this paper. The aim of this study was to show precisely the effects of tourism and catering to the national economy of Serbia. There are data obtained by a research of documentation of Statistical Yearbook of the Republic of Serbia , as well as internal documentation of certain tourist and catering facilities. The results reached suggest that tourism has a particular impact on economic development and economic stabilization, but that this effect is still far more than expected or that which is characteristic of other developed nations coach. Further, the work on the basis of some problems and goals set out for expansive development of the service sector.